Phytoremediation: A Review Focusing on Phytoremediation Mechanisms - Kaushal Jyotsna; Bhasin S.K.; Bhardwaj Punit (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Rapid industrialization and urbanization has led to increased disposal of pollutants such as heavy metals, radio-nuclides, various types of organic and inorganic compounds into the environment. The rapid build-up of toxic pollutants in soil, surface water, and ground water affects natural resources, besides causing major strains on ecosystems and thus pose serious risks to human health. Many physico-chemical processes such as screening, coagulation, activated carbon treatment, ion-exchange electrodialysis, trickling filteration, reverse osmosis and activated sludge digestion have been employed for the treatment of polluted water. But all these methods involve high energy and large capital investments. Recently, Phytoremediation has been employed successfully to clean up ground water pollution and soil-contaminated sites because this method is aesthetically pleasing, solar energy giving and passive technique. The objective of this review paper is to present the various phytoremediation mechanisms such as Phytoextraction, Phytovolatilization, Phytostabilization, Rhizofiltration, Phytodegradation Rhizodegradation for different plant species and their potentials as phytoremediators. Although these techniques have been successfully employed for the treatment of water pollution, yet the commercial application of this technology has to be investigated.